2022
DOI: 10.1007/s11739-022-03000-1
|View full text |Cite|
|
Sign up to set email alerts
|

Usefulness of fibrosis-4 (FIB-4) score and metabolic alterations in the prediction of SARS-CoV-2 severity

Abstract: Despite vaccination programs, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection remains a public health problem. Identifying key prognostic determinants of severity of the disease may help better focus health resources. The negative prognostic role for metabolic and hepatic alterations is established; however, the interplay among different metabolic comorbidities and their interconnections with the liver have never been explored.The objective of this study is to evaluate the impact of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…We found that the liver fibrosis index, as measured using the FIB-4 index, was significantly associated with the risk of poor prognosis, including ICU admission, mechanical ventilation, and mortality, in COVID-19 patients without underlying liver diseases. Our results are consistent with those of previous studies that demonstrated the predictive value of liver function tests, such as ALT and AST levels, for COVID-19 infection [ [11] , [12] , [13] , [14] ]. The liver is a target organ of the SARS-CoV-2 virus and is often affected by the inflammatory response to the infection.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the liver fibrosis index, as measured using the FIB-4 index, was significantly associated with the risk of poor prognosis, including ICU admission, mechanical ventilation, and mortality, in COVID-19 patients without underlying liver diseases. Our results are consistent with those of previous studies that demonstrated the predictive value of liver function tests, such as ALT and AST levels, for COVID-19 infection [ [11] , [12] , [13] , [14] ]. The liver is a target organ of the SARS-CoV-2 virus and is often affected by the inflammatory response to the infection.…”
Section: Discussionsupporting
confidence: 93%
“…Intermediate and high FIB-4 scores had a combined 3-fold increase in severe COVID-19 risk (adjusted OR = 2.95, p < 0.005). Similarly, in a study in Italy (45), the FIB-4 score < 1.45 was associated with lower disease severity (adjusted OR = 0.3, p = 0.01) and mortality (adjusted OR = 0.4, p = 0.04). Contrary to the previous results, do Amaral e Castro and colleagues (46) did not find an association between HS and worse COVID-19 outcomes, although HS was more common among patients with worse outcomes.…”
Section: Covid-19 Severitymentioning
confidence: 70%
“…Park et al [ 7 ] found a cut-off of 4.95 to be a good predictor of mortality. Lombardi et al [ 30 ] recently confirmed the prognostic role of FIB-4 in 382 patients. They showed that a FIB4 < 1.45 is a protective factor against severe SARS-CoV-2 infection and that in patients with at least one metabolic comorbidity, FIB-4 > 1.45 is associated with poorer outcomes.…”
Section: Discussionmentioning
confidence: 97%